Adaptive dead time in high frequency GaN-Inverters with LC output filter - Kohlhepp, Benedikt; Kübrich, Daniel; Tannhaeuser, Marvin; Dürbaum, Thomas (10th International Conference on Power Electronics, Machines and Drives, PEMD 2020, 2020)
Keywords: Gan-inverter; Adaptive dead time; Reverse conduction losses; LC output filter

A detailed investigation of the DC-link voltage ripple in battery-fed PWM inverter systems - Mantzanas, Panagiotis; Bucher, Alexander; Kübrich, Daniel; Pawellek, Alexander; Hasenohr, Christian; Hofmann, H.; Dürbaum, Thomas (International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, PCIM Europe 2019, 2019)

A Fast and Accurate Calculation Method for Predicting the Battery Current Ripple in Battery-Fed PWM Inverter Systems - Mantzanas, Panagiotis; Kübrich, Daniel; Dürbaum, Thomas (21st IEEE Workshop on Control and Modeling for Power Electronics, 2020)

A Fast and Accurate Calculation Method for Predicting the DC-link Voltage Ripple in Battery-fed PWM Inverter Systems - Mantzanas, Panagiotis; Hasenohr, Christian; Dürbaum, Thomas; Bucher, Alexander; Pawellek, Alexander; Kübrich, Daniel; Hofmann, Harald (19th IEEE Workshop on Control and Modeling for Power Electronics, COMPEL 2018, 2018)
Keywords: Voltage ripple; Power density; PWM inverter; Battery inductance and resistance; Analytical calculation; DC-link capacitor; Battery-fed

A Fast Calculation Tool for the Design of PFC Converters - Method and Application - Dürbaum, Thomas; Kübrich, Daniel; et al. (PCIM Conference, May/June 2006, Nuremberg, Germany, 2006)
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.lselek.afastc

A fast calculation tool for the design of PFC converters - Method and application - Kübrich, Daniel; et al. (IECON 2005: 31st Annual Conference of IEEE Industrial Electronics Society, 2005)

A fast calculation tool for the design of PFC converters - Method and application - Kübrich, Daniel; et al. (IECON 2005: 31st Annual Conference of IEEE Industrial Electronics Society, 2005)

A fully automated measurement set-up for the determination of the reverse recovery behaviour of ultra-fast diodes - Stahl, Jürgen; Kübrich, Daniel; Dürbaum, Thomas; Leicht, Anne-Christine; Patz, Janina (2011 14th European Conference on Power Electronics and Applications, EPE 2011, 2011)
Keywords: Diode; Reverse recovery; Measurement

A Fully Automated Measurement Set-up for the Determination of the Reverse Recovery Behaviour of Ultra-Fast Diodes - Stahl, Jürgen; Kübrich, Daniel; Dürbaum, Thomas; Leicht, Anne-Christine; Fischer, Janina (European Conference on Power Electronics and Applications (EPE), August 2011, 2011)
Often data sheets provide only poor information about the recovery behavior of ultra-fast diodes. On the other hand, existing diode models do not predict the real characteristic of all diodes. Nevertheless, due to its importance, this behavior needs to be known and therefore measured. For this purpose, a fully automated measurement set-up for determining the reverse recovery characteristic of ultra-fast diodes in an accurate manner was designed and is described here. All the data obtained is immediately transferred into MATLAB and therefore available for further calculation, model building and model validation. Since the whole set-up is automated, a complete field of variations in the reverse voltage, the forward current, the temperature, and the rate of current drop di/dt can be easily applied to the tested diode. Hence, a lot of information can be obtained effortlessly. This uncomplicated methodology makes it readily available for circuit designers, allowing them to predict the contribution of the reverse recovery of rectifiers to the total losses more accurately. In addition, a real comparison of different diodes at many operation points is possible. © 2011 EPE Association - European Power Electr.
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.afully
Keywords: Diode; Measurement; Reverse recovery

Analysis of the Flyback Converter Utilizing a Transformer with Stepped Air-Gap - Mantzanas, Panagiotis; Kübrich, Daniel; Barwig, Markus; Dürbaum, Thomas (2016 International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, PCIM Europe 2016, 2016)

Analytical Calculation of the Current Depending Inductance of a Stepped Air Gap Inductor - Stenglein, Erika; Kübrich, Daniel; Albach, Manfred (18th European Conference on Power Electronics and Applications (EPE 2016 ECCE Europe), 2016)
Magnetic devices are essential components in the field of power electronics. Exploiting the non-linear behavior of inductors and transformers offers the great merit of increasing the performance of switch mode power supplies. For instance, the light-load efficiency of a buck voltage regulator can be improved by using a non-linear inductor with stepped air gap. Moreover, non-linear chokes can be used for passive power factor correction or are employed in solar PV systems. For an optimal design, however, a controlled decrease in inductance at a larger current is required. Such a characteristic is displayed by inductors with stepped air gaps. To optimize the gap geometry, the knowledge of the exact behavior of the non-linear choke is crucial. As simulation tools require rather long computation times in order to calculate the non-linear characteristic, the authors chose a different approach. This paper demonstrates the analytical calculation of the current depending inductance of pot cores with stepped air gap. By solving a boundary value problem the magnetic vector potential inside the winding area is obtained assuming linear core material. Subsequently, the non-linearity of the core material is incorporated by decomposing the original non-linear problem into linear subproblems. Following this, the solution of the original problem is composed by using the solutions of the linear subproblems. Once the magnetic vector potential as a function of inductor current has been determined, the current depending inductance can be calculated. Results derived from both simulations with COMSOL Multiphysics and measurements show good agreement with the theoretical predictions.
Keywords: Passive component; Magnetic device; Device Modeling; Measurement

Analytical calculation of the current sharing in copper coils with parallel windings - Leicht, Anne-Christine; Albach, Manfred; Spang, Matthias; Kübrich, Daniel (International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, PCIM Europe 2012, 2012)

A novel approach to reduce losses in boost PFC stage of a 90W-adapter - Schmidt, Eva; Kübrich, Daniel; Dürbaum, Thomas (2017 International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, PCIM Europe 2017, 2017)

Application of Non Linear Inductance in Passive Mains Harmonic Reduction Circuits - Kübrich, Daniel; et al. (PCIM 2005, Nürnberg, Germany, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.lselek.applic

Application specific efficiency improvement for an industrial point of load converter - Tech, Hendrik; Oeder, Christian; Kübrich, Daniel; Dürbaum, Thomas (IEEE Applied Power Electronics Conference and Exposition (APEC), March 2013, 2013)
Today, many electrical applications use the DC-DC buck converter topology as point of load (POL) converter with synchronous rectifiers to provide the desired output voltage for different loads and components [1-3]. While its efficiency is usually optimized for high output powers, in case of low and mid power it is often off the optimum. Nevertheless, since many applications force these converters to operate at part load condition most of the time, the system's overall power consumption can be reduced noticeably by optimizing the efficiency at its main operating point. This paper deals with the specific efficiency improvement of an existing industrial POL converter (P o,max = 60 W) towards its main operating point at part load with Po = 15 W. In a first step, the converter is analyzed in the time-domain by means of a sampled data modeling (SDM) approach in order to simulate and predict its behavior as accurate as possible. In a second step, based on the derived converter model the POL is optimized for Po = 15 W by simulations using the SDM model. Finally, practical measurements are performed in order to verify the correctness of the identified options for improvements. © 2013 IEEE.
UnivIS-Import:2015-03-09:Pub.2013.tech.IE.lselek.applic

A Programmable Pulse Generator for the Investigation of Dead Time Effects in Half Bridges - Kübrich, Daniel; et al. (PCIM Conference, May/June 2006, Nuremberg, Germany, 2006)
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.lselek.aprogr

Automated Test Set-up for Efficiency Measurements of Switch Mode Power Supplies - Dürbaum, Thomas; Kübrich, Daniel; et al. (PCIM Conference, May 2008, 2008)
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.lselek.automa

Automated Test Set-up for Reverse Recovery Characterization of Ultrafast Diodes - Stahl, Jürgen; Kübrich, Daniel; Dürbaum, Thomas (IEEE Applied Power Electronics Colloquium (IAPEC), 2011)
Often data sheets provide only poor information about the recovery behavior of ultra-fast diodes. On the other hand, existing diode models do not predict the real characteristic for all diodes. Nevertheless, due to its importance, this behavior needs to be known and therefore measured. For this purpose, a fully automated measurement set-up for determining the reverse recovery characteristic of ultra-fast diodes in an accurate manner was designed and is described here. All the data obtained is immediately transferred into MATLAB and therefore available for further calculation, model building and model validation. Since the whole set-up is automated, a complete field of variations in the reverse voltage, the forward current, the temperature, and the di/dt can be easily applied to the tested diode. Hence, a lot of information can be obtained effortlessly. This uncomplicated methodology makes it readily available for circuit designers, allowing them to predict the contribution of the reverse recovery of rectifiers to the total losses more accurately. In addition, a real comparison of different diodes at many operation points is made possible. © 2011 IEEE.
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.automa

Automatic Measurement of the Reverse Recovery Behavior of Ultra-Fast Diodes - Stahl, Jürgen; Kübrich, Daniel; Oeder, Christian; Pawellek, Alexander; Dürbaum, Thomas (Energy Conversion Congress and Exposition (ECCE), September 2011, 2011)
Often data sheets provide only poor information about the recovery behavior of ultra-fast diodes. On the other hand, existing diode models do not predict the real characteristic for all diodes. Nevertheless, due to its importance, this behavior needs to be known and therefore measured. For this purpose, a fully automated measurement set-up for determining the reverse recovery characteristic of ultra-fast diodes in an accurate manner was designed and is described here. All the data obtained is immediately transferred into MATLAB and therefore available for further calculation, model building and model validation. Since the whole set-up is automated, a complete field of variations in the reverse voltage, the forward current, the temperature, and the di/dt can be easily applied to the tested diode. Hence, a lot of information can be obtained effortlessly. This uncomplicated methodology makes it readily available for circuit designers, allowing them to predict the contribution of the reverse recovery of rectifiers to the total losses more accurately. In addition, a real comparison of different diodes at many operation points is made possible. © 2011 IEEE.
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.automa_8

Averaged large signal model of boost power factor corrector in boundary conduction mode - Schildbach, Christian; Kübrich, Daniel; Dürbaum, Thomas (2009 13th European Conference on Power Electronics and Applications, EPE '09, 2009)
Keywords: Measurement; Converter control; Power factor correction; Modeling; Simulation

Averaged large signal model of boost power factor corrector in boundary conduction mode - Schildbach, Christian; Kübrich, Daniel; Dürbaum, Thomas (EPE Power Electronics and Motion Control Conference, 2009)
A modeling approach of a power factor correction circuit operating in boundary conduction mode is presented. The PFC is controlled by a constant on-time of the switch. The effect of valley switching is simplified and taken into account as dead-time to generate a large signal model. On the basis a small signal model for the constant on-time controlled PFC voltage loop is derived. The large and small signal models are compared to measurements of the transfer function. For performing this low frequency transfer functions measurement a set-up using an oscilloscope and functional generator is described.
UnivIS-Import:2015-03-09:Pub.2009.tech.IE.lselek.averag
Keywords: Converter control; Measurement; Modeling; Power factor correction; Simulation

Balancing Unit for Proper Characterization of a Modified LISN for Effective EMI Noise Separation - Stahl, Jürgen; Kübrich, Daniel; Dürbaum, Thomas; et al. (International Conference on Power Electronics Drives and Motion PCIM, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.balanc

Characterisation of an effective EMI noise separation including a standard LISN - Stahl, Jürgen; Kübrich, Daniel; Dürbaum, Thomas (Electromagnetic Theory (EMTS), 2010 URSI International Symposium, 2010)
The compliance with standards calls for proper designed EMI filters. EMI typically comprises common mode (cm) and differential mode (dm) noise. A systematic optimization of EMI filters requires the knowledge of the contribution and distribution of these two noise sources. The paper discusses different methods that allow the independent measurement of cm and dm noise. One suitable method described in detail integrates the separation set-up into the Line Impedance Stabilization Network (LISN). However, a correct interpretation of the measured results requires a characterization of the unavoidable crosstalk of the complete set-up - i.e. the measured level at the dm output in case of pure cm excitation and vice versa. As shown in this paper, the implementation of a standard LISN introduces the highest amount of imperfections causing the undesired crosstalk. Thus, for the first time, this paper describes the characterization of the whole set-up including the LISN. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.charac

Characterization of a modified LISN for effective separated measurements of common mode and differential mode EMI noise - Stahl, Jürgen; Kübrich, Daniel; Bucher, Alexander; Dürbaum, Thomas (Energy Conversion Congress and Exposition (ECCE), 2010 IEEE, 2010)
The compliance with standards calls for proper designed EMI filters. EMI typically comprises common mode (cm) and differential mode (dm) noise. A systematic optimization of EMI filters requires the knowledge of the contribution and distribution of these two noise sources. The paper discusses different methods that allow the independent measurement of cm and dm noise. One suitable method described in detail integrates the separation set-up into the Line Impedance Stabilization Network (LISN). However, a correct interpretation of the measured results requires a characterization of the unavoidable modal conversion of the complete set-up - i.e. the measured level at the dm output in case of pure cm excitation and vice versa. As shown in this paper, the implementation of a standard LISN introduces a high amount of imperfections causing the undesired modal conversion. Thus, for the first time, this paper describes the characterization of the whole set-up including the LISN. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.charac_0
Keywords: Characterization of noise separation; Common mode (cm); Differential mode (dm); EMC; EMI; LISN; Noise separation

Common Mode of Inverters: Survey and Study of Filter Placement on Grid and Load Side - Kohlhepp, Benedikt; Dobusch, Julian; Kübrich, Daniel; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2022)
Inverters driving motors fed by the grid require PFC stages with a suitable filter. Designing the filter requires knowledge of the noise level. As cm-noise prediction of inverters is quite difficult, this paper studies an inverter’s cm-noise by experiments. It is shown that high levels can be expected from inverters, when no filter is applied. Thus, this paper analyzes the cm-noise paths and derives a filter placed between grid and inverter. An alternative position of the filter is between inverter and motor. This configuration requires a smaller common mode choke to comply with EMI standards.
CRIS-Team Scopus Importer:2022-06-10

Comparison of different design methods for the parallel resonant converter - Kübrich, Daniel; et al. (EPE-PEMC 2006: 12th International Power Electronics and Motion Control Conference, 2007)

Comparison of different design methods for the parallel resonant converter - Kübrich, Daniel; et al. (EPE-PEMC 2006: 12th International Power Electronics and Motion Control Conference, 2007)

Comparison of First Harmonic Approximation with exact Solution in case of a Series Resonant Converter - Dürbaum, Thomas; Kübrich, Daniel; et al. (PCIM Conference, May/June 2006, Nuremberg, Germany, 2006)
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.lselek.compar

Consideration of Conduction Losses for the Series Resonant Converter by Means of a Simple Extension to the SPA Approach - Bucher, Alexander; Dürbaum, Thomas; Kübrich, Daniel; Schmid, Markus (Power Electronics and Motion Control Conference, September 2008, 2008)
The cumbersome derivation of the steady-state characteristics of resonant converters can be simplified by means of the state-plane analysis. Under the assumption of ideal components, a closed-form solution can be derived in case of the series resonant converter above the resonant frequency. However, losses due to parasitic resistances cannot be easily included within this approach. Nevertheless, a more precise prediction of the converter's output characteristics taking the conduction losses into account is desirable. Therefore this paper describes a simple extension to the regular approach that leads to better agreement with measurements. This approach is based on the results derived under ideal assumptions, thus avoiding a more complicated and tedious analysis including the conduction losses. © 2008 IEEE.
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.lselek.consid
Keywords: Modelling; Resonant converter; ZVS converter

Coupling Mechanisms - EMC experiment demonstrations - Albach, Manfred; Kübrich, Daniel; et al. (IEEE International Symposium on Electromagnetic Compatibility, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.lselek.coupli

Current distribution in copper coils with parallel windings - Leicht, Anne-Christine; Albach, Manfred; Spang, Matthias; Kübrich, Daniel (2011 14th European Conference on Power Electronics and Applications, EPE 2011, 2011)
Keywords: Device modeling; Conduction losses; Passive component; Magnetic device

Dynamically adapting equivalent circuit model describing the EMI behaviour of magnetic components - Diepold, Fabian; Kübrich, Daniel; Leicht, Anne-Christine; Albach, Manfred (2013 15th European Conference on Power Electronics and Applications, EPE 2013, 2013)
Keywords: EMC/EMI; Device modeling; software; passive component; transformer

Effect of the EMC requirements on the power supply design for modern railway systems [Auswirkung der EMV-Anforderungen auf den Netzteilentwurf für Modellbahnsysteme] - Kübrich, Daniel; Albach, Manfred; Schöllkopf, K. (Internationale Fachmesse und Kongress fur Elektromagnetische Vertraglichkeit, EMV 2016 - International Trade Fair and Congress for Electromagnetic Compatibility, EMV 2016, 2016)

Efficiency improvement of a flyback converter by employing a stepped air-gap transformer - Mantzanas, Panagiotis; Barwig, Markus; Kübrich, Daniel; Dürbaum, Thomas (18th European Conference on Power Electronics and Applications, EPE 2016 ECCE Europe, 2016)
Keywords: Design; DC power supply; Transformer; Efficiency

Electron beam-based additive manufacturing of Fe93.5Si6.5 (wt.%) soft magnetic material with controllable magnetic performance - Yang, Jing; Fu, Zongwen; Ye, Jihui; Kübrich, Daniel; Körner, Carolin (Scripta Materialia, 2022)
Crack-free Fe-Si soft magnetic material with various microstructural features is additively manufactured by means of Electron beam Powder Bed Fusion (E-PBF). Owing to different microstructural features caused by using different processing parameters, E-PBF-processed Fe93.5Si6.5 (wt.%) shows adjustable magnetic performance (e.g., power losses and saturation magnetic flux density) and various electrical properties. The correlation between the processing parameters used during E-PBF and the corresponding microstructural features as well as the resulting magnetic and electrical properties is discussed.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Electron beam Powder Bed Fusion; Fe-Si soft magnetic material; Magnetic properties; Microstructure

EMC Focused Half-Bridge Characterization and Modeling - Dobusch, Julian; Konarski, Philipp; Kübrich, Daniel; Dürbaum, Thomas (EMC Europe 2019 - 2019 International Symposium on Electromagnetic Compatibility, 2019)
Power electronic circuits are a major source of Electromagnetic Compatibility (EMC) problems. The increased switching speed of modern semiconductor devises based on Silicon Carbide (SiC) and Gallium Nitride (GaN) further aggravates this issue. Thus, the importance of including EMC aspects in the design phase of a power electronic circuit is high and a reliable simulation model is very useful for rapid circuit testing and identification of the source of interference. However, the influence of parasitic components represents a crucial part of the coupling paths and thus has to be considered. This paper covers the development of a highly accurate simulation model including these parasitics. A major concern is the measurement of coupling capacitances which form an essential contribution to the model.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Electromagnetic Compatibility; Half-Bridge; Parasitic Components; Power Electronics

ESD Laboratory for Power Electronics Students - Kübrich, Daniel; et al. (EPE 2005, 2005)
Since the usage of microelectronic components and IC's in electronic systems is growing year by year and reliability is always an issue, the designer has to be aware of possible failures of the components. The ESD (electrostatic discharge) phenomenon arouses more and more interest as these parts are sensitive to short time over voltages. Simulations to predict the effect of ESD in the actual power electronics circuitry are not possible as sufficient models for the components and the complete circuit configuration are not available. Experiments with ESD in conjunction with power electronic devices should make students aware of possible impacts of ESD pulses and methods to protect devices and circuitry. In this paper four experiments together with simple test circuits are presented, which show different aspects of ESD stress like the typical current and voltage wave forms of ESD pulses, system malfunction, pre deterioration and total damage of components.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.lselek.esdlab
Keywords: Education methodology; Education tool; EMC/EMI; MOSFET; Teaching

Evaluating EMI of Unshielded Cables in High Frequency GaN Inverter Application - Dobusch, Julian; Kübrich, Daniel; Dürbaum, Thomas; Diepold, Fabian (2021 Joint IEEE International Symposium on Electromagnetic Compatibility Signal and Power Integrity, and EMC Europe, EMC/SI/PI/EMC Europe 2021, 2021)
Inverters in VSDs represent a common source of EMI. The steep voltage slopes of modern power electronics with their high frequency share can cause radiated emissions. Therefore, shielded motor cables are used to minimize these emissions. However, in order to reduce costs, unshielded cables are an attractive option. This paper analyses an inverter setup with different motor cables. A measurement setup is presented in order to investigate the proper PE connection for complying with the standards.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Cable shielding; Electromagnetic Compatibility; Inverters; Radiated emissions

Evaluation of power LEDs and their efficiency by driving them with currents typical to switch mode power supplies - Dürbaum, Thomas; Kübrich, Daniel; et al. (PCIM Conference, May 2007, Nuremberg, Germany, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.lselek.evalua

Evaluation of power LEDs and their efficiency by driving them with currents typical to switch-mode power supplies - Weiland, Manuel; Schmid, Markus; Kübrich, Daniel; Dürbaum, Thomas (Proceedings of Power Electronics Intelligent Motion Power Quality Conference (PCIM), 2007)
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.leen.evalua

Evaluation on the Efficiency of Power LEDs Driven with Currents Typical to Switch Mode Power Supplies - Schmid, Markus; Kübrich, Daniel; Weiland, Manuel; Dürbaum, Thomas (Conference Record - IAS Annual Meeting (IEEE Industry Applications Society), 2007)
Electronic ballasts are necessary to use light emitting diodes (LEDs) for illuminating purposes powered from the mains. As a consequence this paper shows an examination of two white LEDs considering the resulting losses in luminous efficiency if the LEDs will be driven with different current waveforms as they typically occur in switch-mode power supplies. Therefore it is possible to estimate to which extend more circuitry effort is advisable. © 2007 IEEE.
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.lselek.evalua_4
Keywords: Electronic ballast; General illumination; Power LED

Experimental Study of the Coss-Losses Occurring During ZVS Transitions – Emphasis on Low and High Voltage GaN-HEMTs - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas (CIPS 2020, 2020)
GaN-HEMTs offer completely new possibilities for the development of advanced power electronics. GaN devices enable, due to the lower parasitics, higher switching frequencies. However, high efficiency at high frequent operation requires ZVS. It is typically assumed that the ZVS transitions are lossless. However, at least in case of Si-SJ-MOSFET experiments show that sometimes losses occur during charging and discharging of the output capacitances. For this reason, this paper examines the losses occurring during ZVS by employing Sawyer Tower measurements of GaN devices. Losses are meas-ured depending on the amplitude of the Drain-Source voltage and frequency, finding that these are negligibl

Extraction of Parasitic Elements of a Printed Circuit Board applied to a GaN Half-Bridge - Kohlhepp, Benedikt; Faber, Samuel; Kaiser, Jeremias; Kübrich, Daniel; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2022)
Modern semiconductors like GaN enable high efficient converter designs and fast switching transitions. In order to achieve full performance of these components in terms of switching behavior, parasitic inductances of the switching cell must be accurately known and minimized, since they have a significant influence on the switching transitions. Due to optimized device packages and PCB layouts, these are in the range of nH or even pH, which make accurate measurements very difficult or impossible. Thus, field simulations are the only way to obtain self and mutual inductances of the commutation loop as well as of the gate loops. This paper shows that commutation loop inductances below 1 nH are possible. The common source inductance, which represents the common conductive path as well as mutual couplings, is in the range of pH for a GaN-half-bridge.
CRIS-Team Scopus Importer:2022-06-10

Flyback converter with a stepped air-gap transformer - Mantzanas, Panagiotis; Barwig, Markus; Kübrich, Daniel; Dürbaum, Thomas (Epe Journal, 2018)
Keywords: design; Flyback converter; efficiency; saturable transformer; nonlinear magnetizing inductance; stepped air-gap

Fully Automated Measurement Set-up for Ultra-Fast Recovery Diode Testing - Stahl, Jürgen; Kübrich, Daniel; Dürbaum, Thomas; Oeder, Christian (IEEE Applied Power Electronics Conference and Exposition (APEC), 2011)
Often data sheets provide only poor information about the recovery behavior of ultra-fast diodes. On the other hand, existing diode models do not predict the real characteristic for all diodes. Nevertheless, due to its importance, this behavior needs to be known and therefore measured. For this purpose, a fully automated measurement set-up for determining the reverse recovery characteristic of ultra-fast diodes in an accurate manner was designed and is described here. All the data obtained is immediately transferred into MATLAB and therefore available for further calculation, model building and model validation. Since the whole set-up is automated, a complete field of variations in the reverse voltage, the forward current, the temperature, and the di/dt can be easily applied to the tested diode. Hence, a lot of information can be obtained effortlessly. This uncomplicated methodology makes it readily available for circuit designers, allowing them to predict the contribution of the reverse recovery of rectifiers to the total losses more accurately. In addition, a real comparison of different diodes at many operation points is made possible. © 2011 IEEE.
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.fullya

GaN-Half-Bridge for Core Loss Measurements under Rectangular AC Voltage and DC Bias of the Magnetic Flux Density - Stenglein, Erika; Kohlhepp, Benedikt; Kübrich, Daniel; Albach, Manfred; Dürbaum, Thomas (IEEE Transactions on Instrumentation and Measurement, 2020)
An accurate calculation of core losses is essential for the design of switched-mode power supplies. However, such predictions remain a challenge as core losses depend on various parameters, e.g., the waveform of the magnetic flux density, including its fundamental frequency and dc bias. To investigate the influence of dc bias, core loss measurements usually impose a dc current and, thus, dc bias of the magnetic field strength on ungapped toroid samples. However, hardware designers require the ac and dc excitation of the magnetic flux density. Therefore, this article proposes a half-bridge configuration to impose rectangular ac voltages on the core under test (CUT). By performing a pulsed operation in combination with an iteration method, the desired ac and dc excitation of the magnetic flux density can be obtained. GaN-HEMTs have been applied as they allow a printed circuit board design with low parasitic inductances and thus avoid ringing. The measurement setup is able to characterize magnetic materials at high frequencies for triangular magnetic flux density waveforms, including dc bias and different duty cycles. In addition, the influence of magnetic history on core losses can be studied, an issue usually not addressed in the literature. Moreover, the relationship between the dc bias of the magnetic field strength and the dc bias of the magnetic flux density is investigated. A simple functional approach, e.g., by using the initial magnetization curve, does not suffice to describe this relationship. Accordingly, core losses should be derived as a function of dc bias of the magnetic flux density for the results to be of practical use to hardware designers.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Core loss; dc bias; half-bridge; hysteresis; measurement; rectangular voltage

GaN-HEMT Based Test Setup for Measurement of Core Losses Under DC-Bias - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas (ETG-Fachbericht, 2022)
For power electronics designers, accurate magnetic core loss predictions play a major role in converter design and optimization. Unfortunately, loss predictions are still a difficult task, since manufacturers do not provide enough information in their data sheets for the many parameters affecting the losses. Especially, core loss results under DC-bias of the flux density are missing. Thus, this paper presents a method for these core loss measurements. Instead of using the most common AC metering approach, this paper relies on a DC current and voltage measurement at the input of the inductor loss test setup. After introducing the test setup and its operation principle, the instrumentation and its requirements is studied. Measurements with a device under test deliver the core losses under DC-bias, which show an increase of losses of 13% due to DC-bias in flux density. These results demonstrate the necessity to perform core loss measurement under DC-bias.
CRIS-Team Scopus Importer:2022-09-02

Guideline for Hysteresis Curve Measurements with Arbitrary Excitation: Pitfalls to Avoid and Practices to Follow - Stenglein, Erika; Kübrich, Daniel; Albach, Manfred; Dürbaum, Thomas (PCIM Europe 2018; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2018)

Implementation of Current Based Three-Phase CM/DM Noise Separation on the Drive Side - Dobusch, Julian; Kübrich, Daniel; Dürbaum, Thomas; Diepold, Fabian (2018 International Symposium on Electromagnetic Compatibility (EMC EUROPE), Aug. 2018, 2018)
This paper describes a circuit for CM/DM separation of a three-phase system. The method is applied on the load side of an inverter using current probes. In order to obtain reliable measurement results, a separation set-up is build that can be inserted into a given system. The performed characterisation of this set-up is important in order to judge the measured values. After the verification of the separation performance, measurements demonstrate the utility of the set-up.
Keywords: Electromagnetic Compatibility; Inverters; Three-phase electric power; Current measurement; CM/DM Noise separation; IEC61800

Implementation of Voltage Based Three-Phase CM/DM Noise Separation on the Drive Side - Dobusch, Julian; Konarski, Philipp; Kübrich, Daniel; Dürbaum, Thomas (2018 20th European Conference on Power Electronics and Applications (EPE'18 ECCE Europe), Sept. 2018, 2018)
Inverter drive systems have to comply with EMC regulations partly also on the motor side. The design process of corresponding EMI filters requires knowledge about CM and DM contributions. This paper presents a set-up that performs CM/DM separation on the load side. Measurements on a prototype show promising results.
Keywords: EMC/EMI; Adjustable speed drive; Three-phase system; Voltage sensor

Implementation of voltage based three-phase CM/DM noise separation on the drive side - Dobusch, Julian; Konarski, Philipp; Kübrich, Daniel; Dürbaum, Thomas (20th European Conference on Power Electronics and Applications, EPE 2018 ECCE Europe, 2018)
Keywords: «Adjustable speed drive»; «Three-phase system»; «EMC/EMI»; «Voltage sensor»

Inductor design considerations for overload conditions of lc-filters in high frequency gan-inverters - Kohlhepp, Benedikt; Barwig, Markus; Kübrich, Daniel; Roßmanith, Hans; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2020)
High frequency GaN inverters feature high power density and efficiency. Typically, they are used in conjunction with an output filter in order to keep high frequency noise away from the load. During overload conditions, while accelerating or braking, significantly higher output currents occur compared to nominal operation. Without dramatic oversizing the component, this can result in saturation of the filter inductance’s core in case of ferrite. Therefore, this paper proposes an air inductor as filtering element in order to tackle this problem. Small signal impedance measurements as well as results within a real inverter application demonstrate the feasibility of the designed air inductor.
CRIS-Team Scopus Importer:2020-08-28

Industrie-Schaltnetzgeräte im Test Teil 1: stationäre Eigenschaften - Albach, Manfred; Dürbaum, Thomas; Kübrich, Daniel; et al. (Elektronik, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.lselek.indust

Industrie-Schaltnetzgeräte im Test Teil 2: dynamische Eigenschaften - Albach, Manfred; Dürbaum, Thomas; Kübrich, Daniel; et al. (Elektronik, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.lselek.indust_6

Industrie-Schaltnetzgeräte im Test Teil 3: elektromagnetische Verträglichkeit - Albach, Manfred; Dürbaum, Thomas; Kübrich, Daniel; et al. (Elektronik, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.lselek.indust_4

Influence of Generalized Discontinuous Pulse Width Modulation (GDPWM) on the DC-link Current and Voltage Ripple in Battery-fed PWM Inverter Systems - Mantzanas, Panagiotis; Bucher, Alexander; Kübrich, Daniel; Pawellek, Alexander; Hasenohr, Christian; Hofmann, Harald; Dürbaum, Thomas (2020 22nd European Conference on Power Electronics and Applications, EPE 2020 ECCE Europe, 2020)
In battery-fed pulse width modulated inverters, the DC-link capacitor represents a limiting factor in terms of power density. The size of the DC-link capacitor strongly depends on its current and voltage ripple. This paper investigates the modulation method 'Generalized Discontinuous Pulse Width Modulation' regarding DC-link current and voltage ripple in battery-fed pulse width modulated two-level three-phase voltage source-source inverters. 'Generalized Discontinuous Pulse Width Modulation' already proved to be effective in reducing the inverter switching losses. Parameter studies performed in this paper reveal that this modulation method also enables a reduction of the DC-link voltage ripple in comparison to the widely used modulation method 'centered space vector modulation'.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Adjustable speed drive; Passive component; Pulse Width Modulation (PWM); Simulation; Voltage Source Inverters (VSI)

Influence of magnetic history and accommodation on hysteresis loss for arbitrary core excitations - Stenglein, Erika; Kübrich, Daniel; Albach, Manfred; Dürbaum, Thomas (2019 21st European Conference on Power Electronics and Applications, EPE 2019 ECCE Europe, 2019)
When designing inductive components for switched-mode power supplies, the influence of magnetic history on hysteresis loss is customarily assumed to be negligible in steady-state. This, however, does not apply for excitations comprising major and minor loops. This paper demonstrates the significant effects of magnetic history and accommodation on hysteresis loss.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Magnetic device; Measurement; Passive component; Switched-mode power supply

Influence of the battery inductance and battery resistance on the dc-link voltage ripple in battery-fed pwm inverter systems: A detailed normalized investigation - Mantzanas, Panagiotis; Bucher, Alexander; Kübrich, Daniel; Pawellek, Alexander; Hasenohr, Christian; Hofmann, Harald; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2020)
In battery-fed pulse-width modulated inverters, the DC-link capacitor represents a limiting factor in terms of power density. A proper DC-link capacitor design requires an accurate prediction of its voltage and current ripple. Parasitic elements such as the battery/cable resistance and inductance affect the DC-link voltage and current ripple. Unfortunately, only a small number of papers incorporates such parasitic elements. Thus, this paper studies the influence of the battery/cable resistance and inductance on the DC-link voltage ripple. The results of this study are presented in a normalized form. Thus, they can be easily applied to any battery-fed pulse-width modulated inverter application.
CRIS-Team Scopus Importer:2021-04-19

Investigation of the DC-link Capacitor Current Ripple in Battery-fed PWM Inverter Systems - Mantzanas, Panagiotis; Kübrich, Daniel; Dürbaum, Thomas (2019 21st European Conference on Power Electronics and Applications, EPE 2019 ECCE Europe, 2019)
In battery-fed pulse-width modulated inverters, the DC-link capacitor represents a limiting factor in terms of power density. A proper design of a capacitor requires an accurate prediction of its current ripple. Therefore, this paper proposes a fast simulation model for predicting the DC-link capacitor current ripple in battery-fed pulse-width modulated inverters, which takes the influence of the battery/cable resistance and the battery/cable inductance into account. Based on this simulation model, an extensive parameter study is performed investigating the influence of different parameters on the DC-link capacitor current ripple. This study is presented in a normalized form. Thus, the presented results can be easily applied to any battery-fed pulse-width modulated inverter application.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Modelling; Passive component; Pulse Width Modulation (PWM); Voltage Source Inverters (VSI)

Investigation of Turn-Off Behaviour under the Assumption of Linear Capacitances - Kübrich, Daniel; et al. (PCIM Nürnberg 2006, 2006)
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.lselek.invest

Investigation on a DSP-system to digitally control a switching power supply - Kübrich, Daniel; Dürbaum, Thomas; et al. (PCIM Conference, May 2007, Nuremberg, Germany, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.lselek.invest

Linearity evaluation of voltage-based drive side three-phase CM/DM separation - Dobusch, Julian; Kübrich, Daniel; Dürbaum, Thomas (2019 Joint International Symposium on Electromagnetic Compatibility, Sapporo and Asia-Pacific International Symposium on Electromagnetic Compatibility, EMC Sapporo/APEMC 2019, 2019)
Keywords: Electromagnetic Compatibility; CM/DM Noise separation; Linearity; Inverters

Mains harmonic reduction circuits using non linear inductances - Kübrich, Daniel; et al. (2005 European Conference on Power Electronics and Applications, 2005)
Keywords: Harmonics; Device characterization; Passive filter; Passive component; Power factor correction

Mains harmonic reduction circuits using non linear inductances - Kübrich, Daniel; et al. (2005 European Conference on Power Electronics and Applications, 2005)
Keywords: Harmonics; Device characterization; Passive filter; Passive component; Power factor correction

Measurement of Dynamic On-State Resistance of High-Voltage GaN-HEMTs under Real Application Conditions - Kohlhepp, Benedikt; Kuring, Carsten; Peller, Stefan; Kübrich, Daniel (22nd European Conference on Power Electronics and Applications (EPE'20 ECCE Europe), 2020)
GaN-HEMTs gain a lot of attention to power electronics engineers. However, they could exhibit increased on-state resistance due to charge trapping. This paper focusses on measuring this effect for high voltage devices. Measurements reveal an unexpected blocking voltage dependency of on-state resistance. Therefore, a second measurement setup serves as verificatio

Measuring and Modeling of Dynamic On-State Resistance of GaN-HEMTs - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas (2019 21st European Conference on Power Electronics and Applications, EPE 2019 ECCE Europe, 2019)
GaN-HEMTs as switching devices impress with their very good properties and gain therefore a lot of attention from the power electronics community. However, some GaN devices may exhibit increased resistance during on-state due to charge trapping effects. As for designers of switch mode power supplies the internal structure of devices is concealed, measurements are the only way to gain information. This paper shows the measurement of the static on-state resistance of a GaN-HEMT. Furthermore, it quantifies the dynamic on-state resistance by measurement with a novel clamping circuit using a digitizer card with high resolution. Based on these results, it presents an easy to implement method for calculating conduction losses in the presence of dynamic on-state resistance.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Conduction losses; Gallium Nitride (GaN); Measurement; Modelling

Measuring of Dynamic On-State Resistance of GaN-HEMTs in Half-Bridge Application under Hard and Soft Switching Operation - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas; Tannhaeuser, Marvin; Hoffmann, Andreas (2019 IEEE ELECTRICAL POWER AND ENERGY CONFERENCE (EPEC), 2019)
CRIS-Team WoS Importer:2020-10-02

Methods for the Analysis of the Parallel Resonant Converter with Capacitive Output Filter - Kübrich, Daniel; Dürbaum, Thomas; et al. (PCIM Conference, May 2007, Nuremberg, Germany, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.lselek.method

Modification and characterization of a standard LISN for effective EMI noise separation - Stahl, Jürgen; Kübrich, Daniel; Dürbaum, Thomas (International Conference on Electromagnetics in Advanced Applications (ICEAA 2010 - Offshore), 2010)
The compliance with standards calls for proper designed EMI filters. EMI typically comprises common mode (cm) and differential mode (dm) noise. A systematic optimization of EMI filters requires the knowledge of the contribution and distribution of these two noise sources. The paper discusses different methods that allow the independent measurement of cm and dm noise. One suitable method described in detail integrates the separation set-up into the Line Impedance Stabilization Network (LISN). However, a correct interpretation of the measured results requires a characterization of the unavoidable crosstalk of the complete set-up - i.e. the measured level at the dm output in case of pure cm excitation and vice versa. As shown in this paper, the implementation of a standard LISN introduces the highest amount of imperfections causing the undesired crosstalk. Thus, for the first time, this paper describes the characterization of the whole set-up including the LISN. ©2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.modifi

Modulation Method to Reduce Losses in Inverters with LC-Filters - Kohlhepp, Benedikt; Kübrich, Daniel; Tannhaeuser, Marvin; Dürbaum, Thomas (23rd European Conference on Power Electronics and Applications, EPE 2021 ECCE Europe, 2021)
Keywords: Soft switching; Pulse Width Modulation (PWM); Voltage Source Inverter (VSI)

Multi-Resonant LCC Converter - Comparison of Different Methods for the Steady-State Analysis - Bucher, Alexander; Dürbaum, Thomas; Kübrich, Daniel; Hoehne, Silvio (PESC Record - IEEE Annual Power Electronics Specialists Conference, 2008)
Several different approaches for the investigation of the steady-state properties of resonant converters have been published. In addition to solving the occurring equations in the time domain, which turns out to be quite cumbersome, the designer can make use of approximate approaches in the frequency domain. Two of these methods are compared to the exact solution with regard to their accuracy and mathematical complexity within this paper for the multi-resonant LCC converter with inductive output filter. Additionally, a minimized set of nonlinear equations is derived in case of the exact solution based upon the state-plane technique. ©2008 IEEE.
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.lselek.multir

New experimental verification of transformer core saturation occurring in forward converters due to remanence flux density - Stenglein, Erika; Scheder, André; Kübrich, Daniel; Albach, Manfred; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2019)
Typically, application notes and published papers for single-ended forward converters with reset winding only consider the saturation flux density of core materials for the design of the transformer. Disregarding the remanence flux density during the design phase, however, might lead to core saturation during converter operation. First, this paper derives the excitation of the forward transformer core. Measurement results then illustrate the influence of the remanence flux density and the inherent risk of core saturation. Hysteretic material properties should be considered when designing the inductive components of switched-mode power supplies. Therefore, this example is particularly relevant for hardware developers.
CRIS-Team Scopus Importer:2021-04-20

Novel fit formula for the calculation of hysteresis losses including DC-premagnetization - Stenglein, Erika; Kübrich, Daniel; Albach, Manfred; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2019)
In the field of power electronics, optimizing inductive components achieves objectives such as increased efficiency, cost savings and/or miniaturization. However, core loss prediction for arbitrary excitations is quite complex and no comprehensive approach has been developed so far. In particular, the influence of DC-premagnetization cannot be neglected. This paper adopts the volt-amperometric-method to measure hysteresis loss for different excitations and DC-premagnetizations in the magnetic flux density. Moreover, the dependence of hysteresis loss on magnetic history is investigated, an issue that is usually not addressed in literature. Finally, this paper provides a novel easy-to-handle formula to estimate hysteresis loss including DC-premagnetization.
CRIS-Team Scopus Importer:2021-04-20

Novel gan half-bridge configuration for the measurement of core losses under rectangular voltages and DC-bias - Stenglein, Erika; Kohlhepp, Benedikt; Kübrich, Daniel; Albach, Manfred; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2020)
An accurate calculation of core losses under rectangular voltages including DC-bias is useful for the design of switched-mode power supplies. Core loss measurements with DC-bias usually impose a DC current and thus DC-bias of the magnetic field strength on ungapped toroids. However, hardware designers require the AC and DC excitation of the magnetic flux density for the results to be of practical use. Therefore, this paper proposes a novel GaN half-bridge configuration to measure core loss under rectangular voltages at high frequencies. A new combination of pulsed operation and iteration method sets the desired DC-bias of the magnetic flux density.
CRIS-Team Scopus Importer:2020-08-28

PCB Layout Parasitics Extraction of a GaN Half-Bridge: Simulation and Experimental Validation - Kohlhepp, Benedikt; Faber, Samuel; Kübrich, Daniel; Dürbaum, Thomas (25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe), 2023)
Commutation loop inductance is on everyone’s lips in power electronics, due the relevance for switching transitions and switching losses. In most cases, this inductance is obtained by using numerical field simulations. However, confidence in the simulation results requires validation by measurements. Especially for designs employing wide bandgap semiconductors, minimized commutation loop inductance is crucial for full performance of the semiconductors. Applying optimized packages and PCB layouts results in commutation loop inductances below 1 nH, which makes its experimental extraction challenging. Therefore, the paper studies a method for commutation inductance measurement based on a resonance of a modified DC-link capacitor with this inductance. The measurement of a GaN-half-bridge’s commutation loop complies with results from simulation, demonstrating that the measurement method is applicable for commutation inductance in sub-nH rang

Piezoelectric EMI Filter for Switched-Mode Power Supplies - Hubert, Florian; Dorsch, Philipp; Kübrich, Daniel; Dürbaum, Thomas; Rupitsch, Stefan (IEEE Transactions on Power Electronics, 2020)
We introduce a novel electromagnetic interference suppression method based on the piezoelectric effect for switch-mode power supplies (SMPSs). A piezoelectric interference-suppression component (PISC) generates a low-impedance propagation path for conducted emissions at its resonance frequency. This results in an attenuation of a discrete disturbance peak. Besides the resonance frequency, the PISC features capacitive behavior. Thus, PISCs can not only substitute regular capacitors (e.g., Y-capacitors), but also provide selective attenuation at discrete frequencies. Moreover, PISCs have the potential to reduce size, weight, and cost of SMPSs because the filter size can be reduced while still fulfilling electromagnetic interference regulations through the use of the PISC. We proof this concept by integrating the PISC in a flyback converter and investigate the attenuation of the common-mode disturbance. In addition, the influence of frequency shifts for the circuitry and the PISC is evaluated. In our measurements, the PISC suppresses a discrete disturbance peak at the switching frequency by 45 dB, which was found to be 17 dB better than the conventional approach. Furthermore, determining factors for a proper usage in SMPS, such as temperature dependence, safety ratings, etc., were examined, and an appropriate design procedure is given. Finally, typical application scenarios for PISCs are describe
Keywords: Flyback Converter; EMI Filter; Piezoelectric Effect; Interference-Suppression Capacitor

Power Loss Measurement based on Transient Temperature Rise - Kübrich, Daniel; Göttle, Jens; Dürbaum, Thomas (IEEE Applied Power Electronics Conference and Exposition (APEC), 5. - 9. Februar 2012, 2012)
A calorimetric method for the determination of losses by means of transient temperature rise is applied to a basic switching cell. The method generally offers a very short measuring time in combination with high accuracy. However, an appropriate characterization of the set-up is crucial which usually implies a large effort. Hence, a simplified thermal model is introduced which minimizes this effort while still obtaining a high accuracy. In addition an elaborate but easy to use calibration and determination procedure is proposed. The result is a power loss measurement method based on calorimetry with a degree of accuracy which could be hardly reached by an electrical measurement. In comparison to common calorimetric methods the measurement time can be dramatically reduced. The method is used to verify predicted losses of a PFC boost converter. © 2012 IEEE.
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.lselek.powerl_6

Power loss measurement using a fast and accurate open calorimeter - Göttle, Jens; Kübrich, Daniel; Dürbaum, Thomas (PCIM Conference, May 2012, 2012)
A calorimetric method for the determination of losses by means of transient temperature rise is applied to a basic switching cell. The method generally offers a very short measuring time in combination with high accuracy. However, an appropriate characterization of the set-up is crucial which usually implies a large effort. Hence, a simplified thermal model is introduced which minimizes this effort while still obtaining a high accuracy. In addition an elaborate but easy to use calibration and determination procedure is proposed. The result is a power loss measurement method based on calorimetry with a degree of accuracy which could be hardly reached by electrical measurement. In comparison to common calorimetric methods the measurement time can be dramatically reduced. The method is used to verify predicted losses of a PFC boost converter. © VDE Verlag GMBH - Berlin.
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.lselek.powerl

Prediction of the EMC behaviour of switch mode power supplies in boundary conduction mode including switching frequency limitations - Kübrich, Daniel; Schmidt, Martin; Dürbaum, Thomas (EPE Power Electronics and Motion Control Conference, 2009)
The conducted EMC behavior of a single phase PFC converter operating in boundary conduction mode is predicted by an analytical simulation process. The simulation routines are very flexible in use allowing also for simulation of switching frequency limitations, valley switching and valley skipping. The straight forward simulation process for differential mode disturbances including all blocks of the EMC measurement equipment is described in detail. The benefit of this approach is that it can be adapted to every converter type. In this paper it has been applied to predict the differential mode disturbance level of a PFC boost converter operating in boundary conduction mode. The simulated disturbance levels are compared with results of an EMC measurement on a sample PFC converter. Furthermore, the impact of switching frequency limitations on the differential mode EMI behavior is discussed.
UnivIS-Import:2015-03-09:Pub.2009.tech.IE.lselek.predic
Keywords: EMC/EMI; Modelling; Passive filter; Power factor correction; Switched-mode power supply

Prediction of the EMC behaviour of switch mode power supplies in boundary conduction mode including switching frequency limitations - Kübrich, Daniel; Schmidt, Martin; Dürbaum, Thomas (2009 13th European Conference on Power Electronics and Applications, EPE '09, 2009)
Keywords: Modelling; EMC/EMI; Power factor correction; Passive filter; Switched-mode power supply

Prediction of the non-linear behavior of a stepped air gap inductor - Stenglein, Erika; Kübrich, Daniel; Albach, Manfred (17th IEEE Workshop on Control and Modeling for Power Electronics, COMPEL 2016, 2016)
Keywords: boundary value problem; measurement; Inductive component; stepped air gap; non-linear inductance

Radio Disturbance Evaluation of Si-and GaN-Inverters - Kohlhepp, Benedikt; Dobusch, Julian; Kübrich, Daniel; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2023)
Inverters are widely used to drive electrical machines. Due to their switching operation, these devices inevitably generate EMC emissions. The demand for high efficiency leads to fast switching (high du/dt) inverters, which do not only emit conducted EMI but also radiated disturbances. Thus, this paper studies radiated emissions of different inverter configurations by using the easily applicable radio disturbance method instead of the cumbersome and time consuming measurements in a chamber. The study reveals that for conventional Si-inverters, shielding of the cables between inverter and motor as well as a metal case do not deliver a sufficient reduction of emissions below 100 MHz. Recently, GaN-devices are used in inverters. Due to their higher switching speed (higher du/dt) emissions may increase further, while their switching losses are reduced. In order to mitigate low frequency radiated emissions, a LC-filter is required. When applying proper shielding, low emissions at high frequencies can be achieved. The paper demonstrates that the radio disturbance measurement method can be an attractive alternative to the semi anechoic chamber during the development phase.
CRIS-Team Scopus Importer:2024-12-16

Reducing SMPS Size and Losses with a Novel Piezoelectric EMI Filter - Hubert, Florian; Kübrich, Daniel; Dürbaum, Thomas; Rupitsch, Stefan J. (CIPS 2024 - International Conference on Integrated Power Electronics Systems, 2024)
Switch-mode power supplies (SMPS) represent a main contributor of electromagnetic interference (EMI). Reducing the EMI filter size with minimal effort is a complex challenge for SMPS developers. To tackle this challenge, we present a new EMI filter concept based on the piezoelectric effect. By utilizing several mechanical vibration modes, multiple disturbance peaks of an interference spectrum can be suppressed. For demonstration purpose an optimized piezoelectric EMI filter is implemented in a flyback converter and the EMI suppression is investigated. In the experiment, a 36 % lower DC loss and a 55 % volume reduction could be achieved by substituting a conventional Y-capacitor with a piezoelectric EMI filter.<br

Sensitivity analysis of air gap size of non linear inductance in passive mains harmonic reduction circuits - Kübrich, Daniel; et al. (Proceedings of the Power Electronics Specialists Conference 2005, 2005)
Regulations like IEC 1000-3-2 impose limits on the line input current harmonics. Passive solutions to obtain mains harmonic reduction still dominate the consumer and PC market segment. Typically linear inductors are used in this application. However, some inductors found in practical designs operate in the saturation region even at power levels to be tested for compliance. On the other hand, nearly all publications dealing with design of the passive MHR circuits assume a linear inductor. This paper investigates the usefulness of non linear inductors in passive MHR circuits by extracting the non linearity and modeling the inductor. A given non linear inductor was built in a typical bridge rectifier - electrolytic capacitor configuration. The measurements confirm the compliance with the regulation. A comparison of the measurement with simulations based on the derived model reveals the usefulness of the model. Thus simulations allow for a sensitivity analysis of the air gap size with respect to compliance of the IEC 1000-3-2. This calculation requires a reasonable scaling of the measured inductance for other air gap sizes. The paper describes a suitable scaling method. A MATLAB program simulates the steady state input current wave form of the passive MHR circuit implementing the scaled non linear inductor and verifies whether the regulation is fulfilled or not. The simulations reveal the range of air gap size leading to a valid design. While the linear inductor needs either a larger number of turns in case of a larger air gap or is no longer able to comply with the IEC 1000-3-2 the non linear inductor allows for a certain variation. The sensitivity analysis demonstrates that the non linear inductor allows for some manufacturing tolerance of the air gap if designed accordingly. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.lselek.sensit

Simple Extension to the State-Plane Analysis Approach for the Series Resonant Converter to Include Conduction Losses - Bucher, Alexander; Dürbaum, Thomas; Kübrich, Daniel (PCIM Conference, May 2008, 2008)
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.lselek.simple

Square wave based small signal modeling of frequency controlled converters - Dobusch, Julian; Oeder, Christian; Kübrich, Daniel; Dürbaum, Thomas (18th IEEE Workshop on Control and Modeling for Power Electronics, COMPEL 2017, 2017)
Keywords: DC-DC power converters; Control; Switched Mode Power Supplies; Resonant Converter; Transfer functions; Time-domain analysis

Study of EMI Behavior of a 2-Level GaN-Inverter – Simulation and Measurement - Kohlhepp, Benedikt; Fal, Yassin; Dobusch, Julian; Kübrich, Daniel; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2024)
Wide-bandgap semiconductors are more and more applied in power electronics converters, as these components feature lower parasitics and as a consequence, lower losses compared to their silicon counterparts. The advantage from the power electronics perspective mainly results from the higher du/dt and di/dt during switching operation and the lower on-state resistance. Unfortunately, faster switching transients may result in increased problems regarding the electromagnetic interference (EMI). This fact makes studies regarding the EMI inevitable for power electronic circuits applying e.g. GaN power semiconductors. One way is to study the EMI behavior of converters with a prototype at the workbench. As this method is very time consuming and costly, carrying out EMI simulations during the development phase of the converter is more efficient. Thus, this paper studies a 2-level GaN-inverter regarding conducted emissions. The frequency domain simulations, which are carried out for a simple DC/DC-converter as well as for an inverter with load are validated using measurements with a standardized test setup for conducted emission. The simulations match the results gained by measurement, which proves the validity of the simulation approach.
CRIS-Team Scopus Importer:2025-10-16

Switching loss estimation of gan-hemts by thermal measurement procedure - Kohlhepp, Benedikt; Kübrich, Daniel; Schwanninger, Raffael; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2021)
Modern semiconductors like GaN and SiC enable high efficient power conversion and provide superior switching behavior. For achieving high efficient converter designs, reliable data concerning losses is vital. Due to the high voltage and current slew rates during switching, the conventional double pulse test cannot be beneficially applied when using GaN to gain results concerning switching losses. Thus, this paper proposes a novel procedure to estimate switching losses by means of thermal measurements. A characterization of the test setup using DC currents links the occurring device temperatures during switching operation to power losses. First measurements prove the applicability of the procedure to a 100 V GaN device.
CRIS-Team Scopus Importer:2021-11-05

Switching Loss Measurement-A Thermal Approach Applied to GaN-Half-Bridge Configuration - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas (23rd European Conference on Power Electronics and Applications, EPE 2021 ECCE Europe, 2021)
Keywords: Measurement; Gallium Nitride (GaN); Switching losses

Teaching of ESD phenomena to power electronics students - Kübrich, Daniel; et al. (IEEE Power Electronics Education Workshop 2005, 2005)

Teaching of ESD phenomena to power electronics students - Kübrich, Daniel; Dürbaum, Thomas; et al. (PEEW 2005, 2005)
Reliability and interference immunity are always important issues in power electronics systems. Modern power electronic components are often very sensitive towards electrostatic discharge effects. For power electronic engineers basic knowledge of ESD phenomena and protection precaution against ESD destruction is mandatory. This paper describe a set of low cost experiments for a lab. The aim of this lab is to teach graduate power electronic students the basic source and the further behaviour of electrostatic discharge as well as functional operation faults in an example circuit and fully deterioration and destruction of power semiconductors. All experiments described in the paper are very simple but show some effects quiet nicely. The lab circuits themselves are designed really robust against ESD stress to provide a long lifetime. The main goal of all experiments is to animate the students to think about ESD and to demonstrate the relevance of ESD-protection. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.lselek.teachi

Test Setup for Dynamic ON-State Resistance Measurement of High- And Low-Voltage GaN-HEMTs under Hard and Soft Switching Operations - Kohlhepp, Benedikt; Kübrich, Daniel; Tannhauser, Marvin; Hoffmann, Andreas; Dürbaum, Thomas (IEEE Transactions on Instrumentation and Measurement, 2020)
GaN-HEMTs impress with excellent properties, and therefore power electronics engineers pay a lot of attention to them. However, during switching operation some devices show increased ON-state resistance. Since, for switch mode power supply designers, the internal device structure is not apparent, measuring the ON-state resistance under the targeted operating conditions is the only method to gain this information. In order to characterize the dynamic ON-state resistance, this article proposes a clamping circuit for accurate measurement. Using a high-resolution digitizer card ensures precise results. The presented measurement setup allows to measure the ON-state resistance under hard and soft switching conditions with parameters of the intended application. In inverter applications, each switch works under hard as well as soft switching. Therefore, the transition between these two operating modes must also be studied in detail. Finally, an extension of the clamping circuit is presented allowing measurements with high-voltage GaN-HEMTs as well. The initial results verify the improved setup.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Clamping circuit; dynamic ON-state resistance measurement; high- and low-voltage GaN-HEMTs

Test Setup for Loss Measurements of Inductive Components by using GaN-HEMTs - Kohlhepp, Benedikt; Peller, Stefan; Kübrich, Daniel; Dürbaum, Thomas (2020 IEEE 21st Workshop on Control and Modeling for Power Electronics, COMPEL 2020, 2020)
This paper describes and verifies a measurement setup based on GaN semiconductors to characterize losses of inductive components used in switched-mode power supplies. Due to insufficient datasheet parameters, especially core losses occurring in inductive components cannot be accurately calculated by simulation. Furthermore, proximity losses within windings are difficult to obtain due to inhomogeneous field distributions within inductive components. Therefore, the ability to measure losses of inductive components plays an important role in the development of power supplies. Conventional test setups use the DUT's AC voltage and current to obtain the losses. Based on [1] this paper designs and verifies a circuit that allows for loss measurements of inductive components by only employing DC voltage measurements. After a presentation of the measuring principle and the resulting test setup realization, it is verified by measuring the well-defined losses of an air coil.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Core loss; Half-bridge; Power measurement; Rectangular voltage

Test setup using DC metering approach for loss measurements of inductive components – principle, characterization, validation and application - Kohlhepp, Benedikt; Kübrich, Daniel; Peller, Stefan; Dürbaum, Thomas (Iet Power Electronics, 2021)
Accurate loss estimation of magnetic components is crucial for power electronics engineers. Unfortunately, loss predictions remain a quite challenging task, as these depend on many parameters and manufacturers typically do not deliver a sufficient database for precise loss estimations. Therefore, this paper revisits an approach allowing loss measurements. In contrast to the most common used approach using alternating current (AC) waveforms to gain information about the losses, this approach relies on measuring direct current (DC) voltage and current. After characterizing the experimental setup, air inductors serve as references to validate the approach. In a first step, the test setup is used to extract core losses with and without DC bias by designing a special device under test (DUT) featuring low winding loss. Furthermore, this paper demonstrates that the test setup is also able to gain the overall losses of complete magnetic components by using the DC metering approach.
CRIS-Team Scopus Importer:2021-06-18

The Optimization of Transformers with Air Gapped Toroids - Albach, Manfred; Kübrich, Daniel; et al. (Proceedings APEC 2005, 2005)
In this paper the influence of the winding layout on the core losses and also on the leakage inductance is investigated in transformers with air gapped toroids. An analytical method is used in which the field distribution is calculated by means of orthogonal expansion. Based on these results, some design guidelines are derived in order to optimize these components. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.lselek.theopt

The optimization of transformers with air gapped toroids - Kübrich, Daniel; et al. (20th Annual IEEEApplied Power ElectronicsConference and Exposition, APEC 2005, 2005)

The optimization of transformers with air gapped toroids - Kübrich, Daniel; et al. (20th Annual IEEEApplied Power ElectronicsConference and Exposition, APEC 2005, 2005)

The optimization of transformers with air gapped toroids - Kübrich, Daniel; Albach, Manfred; Stadler, Alexander (Twentieth Annual IEEE Applied Power Electronics Conference and Exposition, 2005. APEC 2005, 2005)
In this paper the influence of the winding layout on the core losses and also on the leakage inductance is investigated in transformers with air gapped toroids. An analytical method is used in which the field distribution is calculated by means of orthogonal expansion. Based on these results, some design guidelines are derived in order to optimize these components.